2005
DOI: 10.1111/j.1440-1819.2005.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of first episode of panic attack among white‐collar workers

Abstract: The purpose of the present study was to elucidate a longitudinal matrix of the etiology for first-episode panic attack among white-collar workers. A path model was designed for this purpose. A 5-year, open-cohort study was carried out in a Japanese company. To evaluate the risk factors associated with the onset of a first episode of panic attack, the odds ratios of a new episode of panic attack were calculated by logistic regression. The path model contained five predictor variables: gender difference, overpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
1
17
1
Order By: Relevance
“…Watanabe et al [23] 1,602 subjects (divided into those experiencing a panic attack within the following year and those without panic)…”
Section: Healthy Controlsmentioning
confidence: 99%
“…Watanabe et al [23] 1,602 subjects (divided into those experiencing a panic attack within the following year and those without panic)…”
Section: Healthy Controlsmentioning
confidence: 99%
“…Basically, the literature is fairly consistent in reporting an excess of negative (exit) events in the 6–12 months preceding depression [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18], schizophrenia [19,20,21,22,23] and anxiety disorders [24,25,26,27,28,29,30,31,32,33]. …”
Section: Introductionmentioning
confidence: 95%
“…[11][12][13][14] Moreover, a longitudinal study recently identified stress as a prospective predictor of first panic attacks among white collar workers. 15 Less attention has been given to the role of stress in maintaining PD or leading to relapse. Life stress is associated with greater symptom severity in patients with PD, 16 and in one study chronic stress was associated with poorer long term outcome from CBT for agoraphobia.…”
Section: Introductionmentioning
confidence: 99%